Polymerization capability of simplified dental adhesives with camphorquinone, phenyl-propanedione and bis-alkyl phosphine photoinitiators - Boniek Castillo Dutra Borges; Rodolfo Xavier de Sousa Lima; Géssica Dandara Medeiros de Souza; Ana Carla Bezerra de Carvalho Justo-Fernandes; Letícia Virgínia de Freitas Chaves; Eduardo José Carvalho Souza-Junior; Isauremi Vieira de Assunção (Universidade Estadual de Campinas, 2018)
Aim: this study aimed to evaluate the degree of conversion (DC) exhibited by novel formulations of dental adhesive systems including camphorquinone (CQ), phenyl-propanedione (PPD), and bis-alkyl phosphine oxide (BAPO) when cured by mono- or polywave light emitting diodes (LEDs). Methods: an adhesive model was formulated by mixing hydroxyethyl methacrylate (HEMA, 40 wt%) and bisphenol A glycidyl dimethacrylate (BisGMA, 60 wt%) in ethanol (30 wt%). Five materials were then formulated by adding the following photoinitiators: CQ (1 mol%), CQ/PPD (0.5/0.5 mol%), CQ/BAPO (0.5/0.5 mol%), PPD (1 mol%), and BAPO (1 mol%). The DC for each material was measured with Fourier transform infrared spectroscopy. Analysis of variance and Tukey's post-hoc test were used to analyze the data (p < 0.05). Results: Except for CQ, the photoinitiators provided a significantly higher DC in the adhesive systems following photoactivation with a polywave LED. Conclusion: The use of alternative photoinitiators and a polywave LED improved the DC of the adhesive systems examined.